Constructing Universities as Organizations: University Reforms in Poland in the Light of Institutional Theory - Kwiek, Marek (My University, 2016)
This chapter shows that apart from changes at the systemic and institutional levels, successful reform implementation struggles with a gradual change in academic beliefs, attitudes and behaviours. Currently, visions of the university proposed by the Polish academic community and visions of it proposed by Polish reformers and policymakers (within ongoing reforms) are worlds apart. I shall study recent reforms in the context of specific academic self--protective narratives being produced in the last two decades (at the collective level of the academic profession) and in the context of the Ivory Tower university ideals predominant at the individual level (as studied comparatively through a large--scale European survey of the academic profession). Institutions change both swiftly, radically – and slowly, gradually. Research literature on institutional change until recently was focused almost exclusively on the role of radical changes caused by external shocks, leading to radical institutional reconfigurations. And research literature about the gradual, incremental institutional change have been emergent for about a decade and a half now (Mahoney and Thelen 2010; Streeck and Thelen 2005, 2009; Thelen 2003). Polish higher education provides interesting empirical grounds to test institutional theories. Both types of transformations (radical and gradual) may lead to equally permanent changes in the functioning of institutions, equally deep transformations of their fundamental rules, norms and operating procedures. Questions about institutional change are questions about characteristics of institutions undergoing changes. Endogenous institutional change is as important as exogenous change (Mahoney and Thelen 2010: 3). Moments in which there emerge opportunities of performing deep institutional reforms are short (in Poland these moments occurred in 2009-2012), and between them there are long periods of institutional stasis and stability (Pierson 2004: 134-135). The premises of theories of institutional change can be applied systematically to a system of higher education which shows an unprecedented rate of change and which is exposed to broad, fundamental reform programmes. There are many ways to discuss the Kudrycka reforms - and "constructing Polish universities as organizations" (rather than traditional academic "institutions") is one of more promising. In this account, Polish universities are under construction as organizations, and under siege as institutions. They are being rationalized as organizations, following instrumental rather than institutional logics. Polish academics in their views and attitudes are still following an institutional logic, while Polish reforms are following the new (New Public Management-led) instrumental logics. Both are on a collision course about basic values. Reforms and reformees seem to be worlds apart. I am discussing the the two contrasting visions of the university and describing the Kudrycka reforms as the reistitutionalization of the research mission of Polish universities. The core of reforms is a new level of funding and governance - the intermediary one (and no longer the state one), with four new peer-run institutions, with the KEJN, PKA and NCN in the lead. Poland has been beginning to follow the "global rules of the academic game" since 2009. I am also discussing two academic self-protection modes agains reforms: (Polish) "national academic traditions" and "institutional exceptionalism" (of Polish HE). Both discourses prevailed for two decades, none seems socially (and politically) acceptable any more. Old myths do not seem to fit new realities. In this context I am discussing briefly and through large-scale empirical data the low connectedness to the outside world of Polish HE institutions, low influence of the government on HE policies and the low level of academic entrepreneurialism, as seen through the EUROAC/CAP micro-level data. The conclusion is that the Kudrycka reforms are an imporant first step only - Poland is too slow in reforms, and reforms are both underfunded and inconsistent. Poland is still accumulating disadvantages as public funding and university reforms have not reached a critical point. Ever more efforts lead to ever less results, as macro-level data show. Consequently, it may be useful to construct universities as organizations in Poland to a higher degree than elsewhere in Europe, and especially in Western Europe.
Keywords: constructing universities as organizations; universities as organizations; academic institutions; reforming universities; higher education reforms; university reforms; institutional theory; organizational studies; complete organizations; rationalization of universities as organizations; Kudrycka reforms; reformy Kudryckiej; multi-level governance; institutionalization; reinstitutionalization; republic of scholars; index of academic entrepreneurialism; KEJN; university autonomy; self-protection against reforms; academic beliefs; academic attitudes; EUROAC; CAP data; confrontational reforms; Polish higher education; Polish reforms; Polish universities; Polish academics; academic profession; Ivory Tower; reformers and reformees; incremental change; gradual institutional change; endogeneous institutional change; James Mahoney; Kathleen Thelen; the formalization of the university; explaining institutional change; reform implementation; Johan P. Olsen; university governance reforms